Effects of Fluctuations in oil Prıces on G7 Country Stock Exchanges - Abubakirova, Aktolkin; Kudabayeva, Lyazzat; Omarova, Aizhan; Taskinbaikyzy, Zhanargul; Saubetova, Bibigul (International Journal of Energy Economics and Policy, 2024)
The aim of the study is to analyze the effects of changes in oil prices, which have an important place among energy resources, on the stock market indices of G7 countries. Since they can be considered as a barometer of the macroeconomic indicators of the G7 countries, the stock market indices of these countries were included in this study and their impact on the fluctuations in oil prices was examined. G7 countries produce 85% of the world's production and constitute 66% of the world's population. 75% of international trade is carried out by the member countries of this group. The share of these countries in international investment is 80%. In this study, the impact of oil price changes on G7 country stock market indices was investigated with monthly frequency data between January 2010 and December 2023. This effect was tried to be found by applying Granger causality test and cointegration test. According to the findings obtained in this study, it was understood that there was no cointegration and the variables did not balance in the long run. On the other hand, according to the Granger causality test, it was determined that the crude oil price was the cause of the stock markets of G7 countries with a significance of 10%.